Early carotid endarterectomy after non-disabling ischaemic stroke: adequate therapeutical option in selected patients - Eckstein, Hans-Henning; Schumacher, Hardy; Laubach, Hans-Heinrich; Ringleb, Peter A.; Forsting, Michael; Dörfler, Arnd; Bardenheuer, Hubert J.; Allenberg, Jens-Rainer (European journal of vascular and endovascular surgery, 1998)
Objective: - To evaluate neurological outcome and long-term results of early carotid endarterectomy (CEA) after nondisabling stroke. - Materials: - Retrospective study between 1980 and 1995 of 56 patients undergoing CEA within 4 weeks of a transient (n = 15) or a permanent non-disabling (n = 41) ischaemic stroke. - Methods: - Analyses of preoperative cerebral CT imaging, neurological outcome (mod. Rankin-scale) and long-term results (life-table analyses according to Kaplan-Meier). - Results: - Incidence of early CEA increased from 1.7% (27 out of 1636) in the period 1980-1993 to 7.8% (29 out of 374) between 1994 and 1995. CEA was indicated after a neurological plateau phase was established (median interval 14 days). Fifty-seven per cent of the CEA patients had a minor ischaemic infarction (area <2 cm), 18% showed a large territorial ischaemic infarction (area 2-5 cm) in cerebral CT imaging. Two patients deteriorated postoperatively (minor stroke rate 4%) but no major stroke or death occurred. Life-table probability of stroke-free survival (mean follow-up 42.7 months) was 94%, 90% and 84%, respectively, after 1, 2 and 5 years. Kaplan-Meier survival rates were 96%, 91% and 86% after 1, 2 and 5 years: - Conclusions: - Early CEA after non-disabling stroke is a safe procedure in selected patients.